2013
DOI: 10.1186/1749-8090-8-77
|View full text |Cite
|
Sign up to set email alerts
|

Significance of intraoperative testing in right-sided implantable cardioverter-defibrillators

Abstract: BackgroundImplantation of implantable cardioverter-defibrillators (ICD) from the left pectoral region is the standard therapeutical method. Increasing numbers of system revisions due to lead dysfunction and infections will consecutively increase the numbers of right-sided implantations. The reliability of devices implanted on the right pectoral side remains controversially discussed, and the question of testing these devices remains unanswered.MethodsIn a prospectively designed study all 870 patients (60.0±14 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Crossing on the right side implies venographic confirmation of RSVC, an additional puncture and increased risk of pneumothorax and increase postprocedural discomfort in right-handed patients. In case of cardioverter defibrillators, right side placement might reduce the efficiency of defibrillation therapies, requiring defibrillation threshold testing [ 23 ]. As a result, there are case reports in which right sided approach was used for lead placement, and the lead was connected to the left side defibrillator pocket through subcutaneous tunneling [ 4 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crossing on the right side implies venographic confirmation of RSVC, an additional puncture and increased risk of pneumothorax and increase postprocedural discomfort in right-handed patients. In case of cardioverter defibrillators, right side placement might reduce the efficiency of defibrillation therapies, requiring defibrillation threshold testing [ 23 ]. As a result, there are case reports in which right sided approach was used for lead placement, and the lead was connected to the left side defibrillator pocket through subcutaneous tunneling [ 4 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 8 of these patients were reimplanted with CRT/CRTD on the right side following removal. Several studies have suggested that although the defibrillation threshold may be elevated in the right implantable cardiac defibrillator (ICD) compared with that noted in the left ICD, it is still considered safe and effective in clinical applications (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…While pacemakers have been routinely implanted from the right side, right‐sided ICD implants are much rarer. For one thing, ICDs are larger and bulkier which can complicate a right‐sided implant, and more importantly, right‐sided ICD implantation can alter the shocking vector in such a way that increases the defibrillation threshold .…”
Section: Discussionmentioning
confidence: 99%